Gap Analysis: Asset and Liability Management at a Bank - Garg, Anju (Journal of Commerce and Trade, 2021)
Market risk-the risk that a sudden change in market prices could affect earnings or capital-can be difficult to measure, but that doesn't make it any less important. One way of capturing a bank's exposure to changing interest rates is Gap Analysis. Gap analysis has largely fallen out of use. Today, gap analysis is most useful as a theoretical tool for communicating issues related to interest rate and liquidity risk. This paper seeks to know about the 'Gap Analysis' and to assess and examine the asset and liability management in a hypothetical bank. The study is entirely based on the availability and utilization of secondary data and literature. The secondary data have been collected from the various published sources such as articles published in distinguished Journals, leading Newspapers, published Financial Reports of RBI and other Banks, Five Year Plans and other reputed books related to Financial Management.